19.5k views
0 votes
Instructions:Simplify.Your answer should contain only positive exponents.

Someone help me 11-12 I have to pass this later at 10pm please help:(​

Instructions:Simplify.Your answer should contain only positive exponents. Someone-example-1
User ChrisJJ
by
4.8k points

1 Answer

1 vote

11) Answer:
-(x^(14))/(y^(13))


(2xy^(-4))/(\left(x^(-4)y^4\right)^3\left(-2\right)x^(-1)y^(-3))


=(2xy^(-4))/(-\left(x^(-4)y^4\right)^3\cdot \:2x^(-1)y^(-3))


=(xy^(-4))/(-\left(x^(-4)y^4\right)^3x^(-1)y^(-3))


=(x^2y^(-4))/(-\left(x^(-4)y^4\right)^3y^(-3))


=(x^2)/(-\left(x^(-4)y^4\right)^3y)


=-(x^(14))/(y^(13))

12) Answer:
-(1)/(u^5v^5)


\left((2u^4v^0)/(-u^(-2)v^(-1)\cdot \:2uv^(-4))\right)^(-1)


=(1)/((2u^4v^0)/(-u^(-2)v^(-1)\cdot \:2uv^(-4)))


=-(1)/(u^5v^5)

User Melih Sahin
by
4.9k points